2020
DOI: 10.1111/desc.13005
|View full text |Cite
|
Sign up to set email alerts
|

States of curiosity and interest enhance memory differently in adolescents and in children

Abstract: A fledgling research field on curiosity has suggested that intrinsic states of curiosity-the desire to acquire new information-enhance learning and memory (for reviews, see Gruber & Ranganath, 2019; Gruber, Valji, & Ranganath, 2019). In line with these findings, neuroimaging studies in adults have demonstrated that 'pre-information' curiosity states elicit increased neural activity in memory-and reward-related brain regions, including the hippocampus and the stria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 87 publications
(218 reference statements)
7
60
2
2
Order By: Relevance
“…Furthermore, the present findings contribute to the nascent literature of how curiosity enhances learning and memory. Prior studies on curiosity-related memory for incidental information used exclusively (i) trivia questions to elicit curiosity and (ii) neutral face images as incidental material (Fandakova & Gruber, 2020;Galli et al, 2018;Gruber et al, 2014;Murphy et al, 2020;Stare et al, 2018). Our findings that the level of curiosity about novel rooms (instead of trivia answers) correlated with memory for incidental daily-life objects (instead of faces) are consistent with previous findings on curiosity-related memory enhancements using the trivia paradigm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the present findings contribute to the nascent literature of how curiosity enhances learning and memory. Prior studies on curiosity-related memory for incidental information used exclusively (i) trivia questions to elicit curiosity and (ii) neutral face images as incidental material (Fandakova & Gruber, 2020;Galli et al, 2018;Gruber et al, 2014;Murphy et al, 2020;Stare et al, 2018). Our findings that the level of curiosity about novel rooms (instead of trivia answers) correlated with memory for incidental daily-life objects (instead of faces) are consistent with previous findings on curiosity-related memory enhancements using the trivia paradigm.…”
Section: Discussionsupporting
confidence: 90%
“…Important for real-world learning, studies have shown that states of high curiosity enhance memory relative to states of low curiosity (e.g., Duan, Fernández, Dongen, & Kohn, 2020;Fastrich, Kerr, Castel, & Murayama, 2017;Gruber, Gelman, & Ranganath, 2014;Kang et al, 2009;Marvin & Shohamy, 2016;Wade & Kidd, 2019). Moreover, states of curiosity also enhance memory for incidental information that is encountered during states of high compared to low curiosity (Fandakova & Gruber, 2020;Galli et al, 2018;Gruber et al, 2014;Murphy, Dehmelt, Yonelinas, Ranganath, & Gruber, 2020;Stare, Gruber, Nadel, Ranganath, & Gómez, 2018). However, studies on the role of curiosity in learning and memory have exclusively employed a trivia paradigm in which trivia questions were used to evoke various levels of curiosity states (for an overview, see .…”
Section: Introductionmentioning
confidence: 99%
“…Memory for the incidental face image was higher when participants anticipated answers with high compared to low curiosity. Therefore, states of high curiosity not only improve learning for topics that piqued an individual's curiosity, but a high-curiosity state can also improve memory of information beyond the target of a person's curiosity (for further replications, see Fandakova & Gruber, 2020;Galli et al 2018;Gruber et al 2014;Stare et al 2018).…”
mentioning
confidence: 99%
“…These studies have been employing a trivia paradigm in which participants anticipate answers to general knowledge questions associated with varying levels of curiosity about the answer. Using a version of the trivia paradigm, we recently investigated whether children between 10 and 14 years showed differential effects of how curiosity and surprise affect memory [20] . We found that younger children (10-12 years of age) and adolescents (12)(13)(14) years of age) demonstrated enhanced memory for answers to trivia questions for which they were curious relative to answers to trivia questions about which they were not curious [20] .…”
Section: • Maturation Of Curiosity-eliciting Brain Functions Might Unmentioning
confidence: 99%